2016
DOI: 10.1097/md.0000000000003115
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Leptin Gene Polymorphisms 223 A/G, 1019 G/A, 492 G/C, 976 C/A, and Anthropometrical and Biochemical Parameters in Children With Obesity

Abstract: The aim of this study was to establish the manner in which the LEPR 223, 1019, 492, and 976 gene polymorphisms influence child obesity.We performed a prospective case-control study on 264 hospitalized children from Romania (Nutrichild study) whom we divided into 2 groups: Group I —143 controls and Group II—121 obese children.The 2 groups were evaluated regarding the anthropometry (MUAC, TST, H/L, hip, and abdominal circumference), paraclinical results (protein, leptin, adiponectin, TNF alfa, IL 6, IL 8, VEGF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
2
30
1
3
Order By: Relevance
“…In a previous study of our team we did not find any correlation between the G allele and gender nor age. [35] Similar results reported by Pyrzak et al [60] highlighted the association between LEPR rs1137101 gene polymorphism and obesity. Even though the data are contradictory, in selected cases it is better to assess the LEPR gene polymorphism and leptin serum levels, taking under consideration the amount of obesity-related complications and their systemic impact.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In a previous study of our team we did not find any correlation between the G allele and gender nor age. [35] Similar results reported by Pyrzak et al [60] highlighted the association between LEPR rs1137101 gene polymorphism and obesity. Even though the data are contradictory, in selected cases it is better to assess the LEPR gene polymorphism and leptin serum levels, taking under consideration the amount of obesity-related complications and their systemic impact.…”
Section: Discussionsupporting
confidence: 70%
“…Recent studies sustain that LEPR rs1137101 (Gln223Arg) is the most frequent one associated with obesity. [3335] Therefore, in some particular cases, it is important to assess these genetic factors, for example in obese pregnant women, those with excessive GWG, or even those who previously had newborns with high birth weight. In the everyday medical practice both FTO and LEPR polymorphisms can be important diagnostic tools, and even prevention ones if they are assessed in pregnant women at risk for having a macrosomic newborn, or a child with increased susceptibility for developing obesity later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Sook‐Ha and Yee‐How showed significant association of 109 K/R and several biochemical and anthropometric parameters (waist circumference, BMI, visceral fat level, subcutaneous fat, total body fat and Leptin level) and the value of Leptin level is higher with K alleles (32.34 ± 42.21 ng/mL) vs (26.70 ± 31.96 ng/mL) for R alleles . Controversy, Marginean et al found a significant association with hip and abdominal circumference among the anthropometric parameters and with the serum level of interleukin 6 and tumour necrosis factor alpha (TNF‐α) but not with serum level of Leptin. For the K109R polymorphism, some studies such as Mizuta et al and Rosmond et al showed a significant association with obesity .…”
Section: Discussionmentioning
confidence: 99%
“…LEPR Gln223Arg (223Q/R) polymorphism was associated with lower Leptin levels in postmenopausal Caucasian women . Recently, Marginean et al showed that the Leptin values associated with the LEPR 223 QQ genotype were higher in obese children vs controls.…”
Section: Discussionmentioning
confidence: 99%
“…Lys 109 Arg (K109R) (rs1137100) Polymorphism of lepR gene in exon 4 by displacement of adenine with guanine in codon 109, and case displacement of lysine amino acid with arginine in extracellular part of receptor might be a reason for leptin ability to bind to the receptor (14).…”
Section: Introductionmentioning
confidence: 99%